Stability of Couette flow in the wide gap of two circular concentric cylinders with rotating inner cylinder and finite growth rate - Takhar, H.S.; Ali, M.A.; Soundalgekar, V.M. (Archives of Mechanics, 1996)
A finite-difference solution for the stability of flow of a viscous fluid in an annular wide-gap space is carried out by taking into account the effects of finite growth rate of the amplification factor σ. The numerical values of the minimum Taylor number Tam and the critical Taylor number Tac for different values of η and for σ ≷ 0 and σ = 0, respectively, are derived and tabulated. The effects of η and σ on the radial component of disturbance and on the cell patterns are shown. It is observed that for increasing σ(> 0), the cell patterns are reduced in size, while for decreasing σ(< 0) they are enlarged.